Trends in the incidence of and survival rates for oral cavity cancer in the Korean population. (7th May 2014) - Choi, SW; Moon, E‐K; Park, JY; Jung, K‐W; Oh, C‐M; Kong, H‐J; Won, Y‐J
<x xml:space="preserve">Abstract</x> Objective This study assessed trends in the incidence of and survival rates for oral cavity cancer in the Korean population. Materials and Methods Data from the Korea Central Cancer Registry were extracted for 10 282 patients diagnosed with oral cavity cancer (C01‐C06) between 1999 and 2010 to evaluate the age‐standardised incidence rate, annual percentage change (APC) and 5‐year relative survival rate (RSR) according to gender and age. Results In males, the incidence rate slightly decreased [APC of −0.2% (P = 0.6427)]; in females, the incidence rate increased [APC of 3.1% (P < 0.05)]. In males and females, the incidence of oral tongue cancer (C02) significantly increased [APC of 2.2% and 4.1%, respectively (P < 0.05)]. This increase in oral tongue cancer incidence was most prominent in the younger age group (<40 years, APC = 6.1%, P < 0.05). The incidence of buccal cheek cancer increased only among males [APC of 4.8% (P < 0.05)]. The 5‐year RSR improved from 42.7% (1993–1995) to 59.5% (2006–2010), corresponding to an increase of 16.8% from 1993 to 2010 (P < 0.05). Conclusion The incidence of oral cavity cancer in females increased, whereas it stabilised or decreased in males. However, the incidence of oral tongue cancer increased in both males and females, especially in the younger age group.